19F NMR for the speciation and quantification of the OH-molecules in complex matrices1. Issue 9 (7th May 2015) - Vlasiou, Manolis; Drouza, Chryssoula
<x xml:space="preserve">Abstract</x> A novel method is demonstrated for the speciation and quantification of the minor OH-molecules in complex matrices in a one pot experiment based on 19F NMR spectroscopy.